2016
DOI: 10.7150/ijbs.15189
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolomic Approach (1H HRMAS NMR Spectroscopy) Supported by Histology to Study Early Post-transplantation Responses in Islet-transplanted Livers

Abstract: Intrahepatic transplantation of islets requires a lot of islets because more than 50% of the graft is lost during the 24 hours following transplantation. We analyzed, in a rat model, early post-transplantation inflammation using systemic inflammatory markers, or directly in islet-transplanted livers by immunohistochemistry. 1H HRMAS NMR was employed to investigate metabolic responses associated with the transplantation. Inflammatory markers (Interleukin-6, α2-macroglobulin) are not suitable to follow islet rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The interaction of metabolites is important to address the question of the influence of changes in concentrations as drawing conclusions from isolated correlations and assumptions may lead to falsepositive results, given that these metabolites share common biochemical anabolic and catabolic pathways. For example, the first step in the essential energy pathway in all cells -the tricarboxylic acid cycle (TCA) -is the conversion of glucose molecules to acetyl CoA, which subsequently, in the intermediate stages of the TCA cycle converts to α-ketoglutarate which, via the alanineaspartate-glutamate pathway, converts to Glx [22]. The Glx further converts into glutamine or GABA [23] (Gln-Glu-GABA cycle).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of metabolites is important to address the question of the influence of changes in concentrations as drawing conclusions from isolated correlations and assumptions may lead to falsepositive results, given that these metabolites share common biochemical anabolic and catabolic pathways. For example, the first step in the essential energy pathway in all cells -the tricarboxylic acid cycle (TCA) -is the conversion of glucose molecules to acetyl CoA, which subsequently, in the intermediate stages of the TCA cycle converts to α-ketoglutarate which, via the alanineaspartate-glutamate pathway, converts to Glx [22]. The Glx further converts into glutamine or GABA [23] (Gln-Glu-GABA cycle).…”
Section: Introductionmentioning
confidence: 99%
“…After activation, they produce various chemokines to attract mononuclear cells and macrophages; in addition, the infiltration of neutrophils leads to the release of cytokines from T cells and macrophages, such as tumor necrosis factor α (TNF-α) and macrophage inflammatory protein 1α. The mobilization of this immune effector could not only expand IBMIR but also induce subsequent adaptive immunity, inducing and enhancing cellular rejection responses ( 50 , 51 ) ( Figure 1 ).…”
Section: Activation and Role Of Macrophages In The Ibmirmentioning
confidence: 99%
“…Generally, they aggregate around the islets at 8 hours and infiltrate them at 12 hours posttransplantation. By 24 hours posttransplantation, the transplanted islets are entirely infiltrated ( 51 ). In islet transplantation, macrophages usually come from three sources: Kupffer cells (KCs) in the recipient’s liver, mononuclear macrophages from the recipient’s bone marrow, and macrophages resident in the donor’s islets.…”
Section: Macrophage Origins In Islet Transplantationmentioning
confidence: 99%
“…It has been reported that up to 70% of grafts were lost in the early stage after transplantation, and islets from 2 to 4 donors are usually needed clinically to meet the needs of 1 recipient. 7,8 The lack of suitable transplantation sites and approaches has become a bottleneck, restricting the development of islet transplantation. 2 Finding an ideal transplantation site that conforms to physiology and is conducive to the survival of islet grafts is 1 of the 3 key issues (β-cell source, transplantation site, and immune protection) that need to be resolved in the field of islet transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that up to 70% of grafts were lost in the early stage after transplantation, and islets from 2 to 4 donors are usually needed clinically to meet the needs of 1 recipient. 7,8 The lack of suitable transplantation sites and approaches has become a bottleneck, restricting the development of islet transplantation. 2…”
Section: Introductionmentioning
confidence: 99%